Analytical characterization and purification of a commercial extract of enzymes: A case study - Llerena Suster, Carlos Rafael (2014)
This paper presents a rational strategy to identify and quantify the components of a commercial extractof the lipase B of Candida antarctica that can be extended to the analytical investigation of other crudeextracts of enzymes. These information provided the fundamental knowledge for the development of amethodology to obtain highly pure and catalytically active CALB enzyme.The commercial extract Lipozyme®was subjected to a series of analytical techniques that alloweddetermining the presence of a non-soluble fraction; nucleic acids; benzoate and sorbate species and amixture of three proteins. Particularly, it is worth noticing that the Bradford assay using CALB as standardinstead of BSA proved to be a more reliable and accurate methodology to quantify the protein con-tent of the assayed enzymatic samples. Size exclusion chromatography coupled with anionic exchangechromatography using a non-conventional, easy to remove buffer system such as ammonia–ammoniumacetate afforded a sample that retains 47% of the proteins (being CALB the only enzymatic component ofthe purified sample) with a hydrolytic activity higher than the crude extract.